Cannabigerol and Cannabicyclol Block SARS-CoV-2 Cell Fusion - Classen, Nica; Pitakbut, Thanet; Schöfbänker, Michael; Kühn, Joachim; Hrincius, Eike R.; Ludwig, Stephan; Hensel, Andreas; Kayser, Oliver (Planta Medica, 2024)
The search for new active substances against SARS-CoV-2 is still a central challenge after the COVID-19 pandemic. Antiviral agents to complement vaccination are an important pillar in the clinical situation. Selected cannabinoids such as cannabigerol, cannabicyclol, cannabichromene, and cannabicitran from Cannabis sativa and synthetic homologues of cannabigerol and cannabicyclol were evaluated for effects on the cell viability of Vero cells (CC50 of cannabigerol and cannabicyclol 40 resp. 38 µM) and reduced virus entry of vesicular stomatitis pseudotyped viruses with surface-expressed SARS-CoV-2 spike protein at 20 µM. In addition to a reduction of pseudotyped virus entry, a titer reduction assay on Vero cells after preincubation of Wuhan SARS-CoV-2 significantly confirmed antiviral activity. Investigations on the molecular targets addressed by cannabigerol and cannabicyclol indicated that both compounds are inhibitors of SARS-CoV-2 spike protein-mediated membrane fusion, as could be shown by a virus-free reporter fusion inhibition assay (EC50 for cannabigerol 5.5 µM and for cannabicyclol 10.8 µM) and by monitoring syncytia formation in Vero reporter cells. Selectivity indices were calculated as 7.4 for cannabigerol and 3.5 for cannabicyclol. Systematic semisynthetic alterations of cannabigerol and cannabicyclol indicated that the side chains of both compounds do not contribute to the observed anti-membrane fusion activity.
Keywords: COVID-19; SARS-CoV-2; Cannabis sativa; Cannabaceae; cannabinoids; cannabigerol; cannabicyclol; membrane fusion; virulence factors